2007
DOI: 10.1007/s10436-007-0072-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospect and Markowitz stochastic dominance

Abstract: Levy and Levy ( , 2004 develop the Prospect and Markowitz stochastic dominance theory with S-shaped and reverse S-shaped utility functions for investors. In this paper, we extend Levy and Levy's Prospect Stochastic Dominance theory (PSD) and Markowitz Stochastic Dominance theory (MSD) to the first three orders and link the corresponding S-shaped and reverse S-shaped utility functions to the first three orders. We also provide experiments to illustrate each case of the MSD and PSD to the first three orders and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…On the other hand, Thaler and Johnson (1990) observed that investors are more risk-seeking on gains and more risk-averse on losses, inferring that investors have a reverse S-shaped utility function. Other academics, for example, Levy and Wiener (1998), Levy andLevy (2002, 2004), Wong and Chan (2008), and Bai et al (2011b) developed their theories based on the assumption that investors possess S-shaped or reverse S-shaped utility function.…”
Section: Investors With Different Shapes In Their Utility Functionsmentioning
confidence: 99%
“…On the other hand, Thaler and Johnson (1990) observed that investors are more risk-seeking on gains and more risk-averse on losses, inferring that investors have a reverse S-shaped utility function. Other academics, for example, Levy and Wiener (1998), Levy andLevy (2002, 2004), Wong and Chan (2008), and Bai et al (2011b) developed their theories based on the assumption that investors possess S-shaped or reverse S-shaped utility function.…”
Section: Investors With Different Shapes In Their Utility Functionsmentioning
confidence: 99%
“…There is an extensive body of literature that outlines the potential pitfalls of eliciting utility functions using certainty equivalent technique types of experiments (Hey et al, 2009;Morone, 2010). Hence, it would be interesting to explore to what extent our findings can be generalized to different preference elicitation methods, as well as stochastic dominance rules (Wong and Chan, 2008), as a more general approach to expected utility maximization.…”
Section: Discussionmentioning
confidence: 96%
“…Studies show that fully concave utility is equivalent to stochastic dominance (SD) and fully convex utility is equivalent to risk-seeking stochastic dominance (RSD) (Wong, 2007;Levy, 2015). On the other hand, S-shaped utility function is equivalent to prospect stochastic dominance (PSD) and reversed S-shaped utility is equivalent to Markowitz stochastic dominance (MSD) (Levy and Wiener, 1998;Levy, 2002, 2004;Wong and Chan, 2008). Recently, Bai et al (2015) has developed tests for SD and RSD and many studies (Qiao et al, 2012 andWong andZhu, 2015) have been using these tests to study preferences of investors with fully concave and fully convex utility, and MSD and PSD tests for S-shaped and reversed S-shaped utility functions (Bai et al, 2012;Fong et al, 2008).…”
Section: Utility Elicitation Approachmentioning
confidence: 99%
“…We also note that there could be many directions for further studies. One of them is to study the preference of other types investors, for example, investors with S-shaped and reversed S-shaped utility functions, see, for example, Wong and Chan [80] and the references therein for more information.…”
Section: Discussionmentioning
confidence: 99%